Biofortification: Leveraging Agriculture to Reduce Hidden Hunger - Bouis, Howarth E.; Islam, Yassir (International Food Policy Research Institute, 2012)
Experts estimate that 2 billion people, mostly in poorer countries, suffer from micronutrient malnutrition, also known as hidden hunger (WHO and FAO 2006). This is caused by a lack of critical micronutrients such as vitamin A, zinc, and iron in the diet. Hidden hunger impairs the mental and physical development of children and adolescents and can result in lower IQ, stunting, and blindness; women and children are especially vulnerable. Hidden hunger also reduces the productivity of adult men and women due to increased risk of illness and reduced work capacity.